2019
DOI: 10.1016/j.ophtha.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Nonfibrotic Scars in the Comparison of Age-Related Macular Degeneration Treatments Trials

Abstract: Objective: To describe changes in visual acuity (VA) and macular morphology at 5 years in eyes with non-fibrotic scars (NFS) identified at 1 year in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT). Design: Prospective cohort study within a randomized clinical trial. Participants: Participants in CATT. Methods: Participants assigned to ranibizumab or bevacizumab and to 1 of 3 dosing regimens were released from the clinical trial protocol after 2 years and recalled at 5 years. NFS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…However, we believe it is paramount to make a distinction between fibrotic scar and nonfibrotic scar. While fibrotic scar development negatively affects the visual outcomes [32][33][34][35], nonfibrotic scars that develop during the first year of treatment appear to be associated with better functional outcomes during follow-up [42]. We also observed that HRM thickness at the initiation of treatment may be an indicator of the scar evolution [23], since thicker HRM has been associated with the development of fibrotic scar [42].…”
Section: Hrm As a Predictive And Prognostic Biomarkermentioning
confidence: 56%
“…However, we believe it is paramount to make a distinction between fibrotic scar and nonfibrotic scar. While fibrotic scar development negatively affects the visual outcomes [32][33][34][35], nonfibrotic scars that develop during the first year of treatment appear to be associated with better functional outcomes during follow-up [42]. We also observed that HRM thickness at the initiation of treatment may be an indicator of the scar evolution [23], since thicker HRM has been associated with the development of fibrotic scar [42].…”
Section: Hrm As a Predictive And Prognostic Biomarkermentioning
confidence: 56%
“…In addition, it is difficult to determine whether prognostic factors truly affect atrophy. For example, atrophy incidence was lower in patients with a nonfibrotic scar than in those with no scar 23 ; however, this observation could be a result of the inability of atrophy to develop in these areas. Furthermore, patient populations in randomized controlled trials do not necessarily reflect real-world patients.…”
Section: Discussionmentioning
confidence: 92%
“…17 Nonfibrotic scar in year 1 was associated with an increased GA incidence at years 2 and 5. 23 Poor baseline VA was associated with an increased risk of development of GA by 5 years. 22 Additional factors associated with a higher incident GA risk at 5 years were older age, hypercholesterolemia, increasing MNV lesion size, RAP lesion, fellow eye GA, and intraretinal fluid.…”
Section: Comparison Of Age-related Macular Degeneration Treatments Trmentioning
confidence: 97%
See 1 more Smart Citation
“…In spite of the efficacy, some cases still showed poor vision outcomes after long-term anti-VEGF therapy. Moreover, several clinical trials also reported that GA developed in neovascular AMD patients after continual treatment with ranibizumab or bevacizumab [ 70 , 71 , 72 , 73 ]. One study even showed that the cumulative incidence of GA increased from the first (12%) to the fifth year (38%) of treatment.…”
Section: Prevention and Intervention Strategies Of Amdmentioning
confidence: 99%